Evaluating the Quality of Screening Process for High-Risk Pregnancies in Paser District, East Kalimantan - Tinaningsih, Morita Dwi; Sulistyowati, Sri; Wijaya, Mahendra; Fithri, An Nisa (South Eastern European Journal of Public Health, 2024)
Health service programme success is measured by maternal mortality. There have been efforts to reduce maternal and neonatal fatalities. Field observations suggest that high-risk pregnancy referral rates are still low, delaying access to better services. Screening for high-risk pregnancies is an operational technique to prevent maternal and newborn emergency issues by allowing early treatment and referral planning. Health cadres and personnel can provide quality information. Lack of knowledge and awareness will harm society, especially pregnant women, in dealing and seeking health care. This study uses descriptive methods to assess high-risk pregnancy screening in Paser Regency, East Kalimantan, by collecting individual data and watching written and verbal behaviour. This research is qualitative and phenomenological. Health workers, ob-gyns, GPs, and pregnant women were informants. The data was collected through interviews from November to December 2023. The research found that high-risk pregnancy screening was still poor due to lack of knowledge, understanding, staff, time, site, and community culture. This research aims to improve high-risk pregnancy screening in Paser Regency, East Kalimantan Province, so that the policy can become permanent and help the planned referral process by motivating, socialising, training health cadres, and requiring cross-sectoral and cross-program support.